2020
DOI: 10.37489/2588-0519-2020-1-35-44
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic burden of COVID-19 in the Russian Federation

Abstract: Аннотация. Цель исследования. Оценка социально-экономического бремени COVID-19 в Российской Федерации (РФ). Материалы и методы. Идентификация и оценка прямых медицинских, прямых немедицинских затрат, а также косвенных расходов в связи с развитием эпидемии коронавирусной инфекции. При расчёте социально-экономического бремени был выбран вариант расчётов с учётом распространённости заболевания. Источниками данных об эпидемиологии заболевания являлись данные Минздрава и данные Правительства РФ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…A study in the U.S.A showed that Covid-19 coronavirus could result in direct medical costs incurred during the infection from $163.3 billion if 20% of the population gets infected to $654.0 billion if 80% of the population gets infected sensitivity ( 12 ). The results of the sensitivity analysis of a study from Russia showed that the extension of the self-isolation period from 1 month to 1.5 and 2 months will lead to an increase in the share of indirect expenses from 40.65% (1 month) to 56.08 (1.5 months) and 67.76% (2 months) of total expenses in connection with the Covid-19 epidemic ( 9 ). The results of a study showed that the long-term economic burden of the disease could be far higher than the cost of developing and delivering vaccines and effective treatments for the disease ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in the U.S.A showed that Covid-19 coronavirus could result in direct medical costs incurred during the infection from $163.3 billion if 20% of the population gets infected to $654.0 billion if 80% of the population gets infected sensitivity ( 12 ). The results of the sensitivity analysis of a study from Russia showed that the extension of the self-isolation period from 1 month to 1.5 and 2 months will lead to an increase in the share of indirect expenses from 40.65% (1 month) to 56.08 (1.5 months) and 67.76% (2 months) of total expenses in connection with the Covid-19 epidemic ( 9 ). The results of a study showed that the long-term economic burden of the disease could be far higher than the cost of developing and delivering vaccines and effective treatments for the disease ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study in the U.S.A indicated that approximately 50% of participants reported income and wealth losses due to the coronavirus, with the average losses being $5,293 and $33,482, respectively ( 8 ). A study in Russia showed that the socio-economic burden of Covid-19 would amount to 4.6 trillion rubles ($71.1 billion) or 4 % of GDP ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…There were two additional studies "awaiting classification". One we were unable to translate [18] and the other we were unable to obtain the full text [19], even after contacting study authors. See the PRISMA Flow Diagram [10]…”
Section: Literature Searchmentioning
confidence: 99%
“…В Российской Федерации смертность медиков на период апрель-май 2020 года измерялась от 5 до 6,83%, в значительной мере превышая таковую в других станах: Иране -1,59%; Италии -0,65%; Великобритании -0,53%; США -0,48%; Испании -0,27%; Германии -0,23% [2,5]. По данным другого информационного агентства, на начало сентября 2020 года [6]. Особо необходимо подчеркнуть, что все вышесказанное, демонстрируя актуальность выбранной направленности изучения вопроса реализации ключевых этических позиций с акцентом на медицинский блок, ни в коей мере не умаляет значения всего комплекса логистичес ких усилий политико-экономического характера, а в своей доминанте отражает глобальную и корневую суть проблемы.…”
Section: фокус изучения ключевых этических позиций в условиях пандемиunclassified